The Importance of Practice Facilitation in Primary Care When Pandemic Takes Hold: Relationships of Resilience. (April 2021) - Hatch, Brigit A.; Ferrara, Laura; Dickinson, Caitlin; Stock, Isabel; Carney, Patricia A.; Fagnan, Lyle J.
The COVID-19 pandemic is unprecedented in recent history as radically and forcefully changing healthcare delivery. Practice facilitators, who often use tools of improvement science, have long played a critical role in supporting routine primary care practice transformation when healthcare system and policy changes occur. However, current events have taken many healthcare systems to the brink of collapse. Our practice facilitation team, which has a long history of sustained primary care partnerships in rural under-resourced settings, is finding creative solutions to carry forward work in research and quality improvement, and the tools of improvement science are well-suited to address rapidly changing demands of primary care during such a crisis. We reflect here on practice facilitation through the pandemic—the value of applied improvement science, and the critical necessity of strong relationships, flexibility, and creativity to support ongoing primary care partnerships.